A utilização de metodologias ativas, através de sequências didáticas, como suporte na aprendizagem de conteúdos de química no ensino médio - Santos, José Adilson Guimarães dos (2020)
The present dissertation presents results of the application of three Didactic Sequences (SD), using active methodologies in classes of a Public High School, in the city of São Miguel dos Campos, Alagoas. The SD were developed after the application and analysis of a semi-structured questionnaire about the learning difficulties of the Chemistry contents and about classes that used active and playful methodologies. 110 students participated in the research, 35 from the 1st year, 35 from the 2nd year and 40 from the 3rd year. The investigation aimed to analyze the importance of using active methodologies in the teaching-learning process of chemistry content with high school students in a public school in Alagoas. The data were collected by observing the participation of each student at the time of applying the DS and by a structured questionnaire applied at the end of the class. The elaboration of the SD was divided in three stages, the first was the bibliographic research of the types of existing methodologies, in the second stage was sought or authors that justify the use of such methodologies and the third stage was the construction, application and analysis of the results of the SD. These steps are described in the 5 chapters of this dissertation. The application of SD occurred in 8 classes from October to December 2019, and was developed in three classes: In the 1st year, the methodology of Cultura Maker was applied, where students built molecular structures using modeling clay and toothpicks; in the 2nd year a didactic board game built by the students was applied, using the content factors that influence the speed of reactions Chemistry to structure the game and in the 3rd year the Educommunication methodology was used with the construction of digitalized photographs and posted on social networks about quantification of carbohydrates and lipids in processed foods. The final product of this dissertation generated a booklet with SD that can serve as another pedagogical tool to assist in Chemistry classes in basic education.